COMBINING ABILITY AND GENE ACTION IN F2 OF TWO- ROWED BARLEY VARIETIES (Hordeum disticum L.) - Mohammed Y. Hameed (Mesopotamia Journal of Agriculture, 2006)
F2 generation for diallel crosses between five barley varieties ( Local Aswad, Tuwwtha, Arta, Zanbaka and Gezira ) were used to estimate combining ability and gene action. Genotypes (parents and F2 hybrids) were sowing in IPA research station in Rabea using Randomized Complete Block Design with three replications. The studied characters were no. of days to heading ,plant height (cm), no. of heads per plant , no. of grains per head , 1000 grains weight (g) and grain yield (g/ plant). Genotypes were significantly different for all studied characters. Analysis of variance for combining ability indicated significant mean squares of general and specific combining ability at 1% level for all studied characters. Tuwwtha variety was good combiner for no. of heading day, no. of grains per head , 1000 grains weight and grain yield. specific combining ability effects was significant for grain yield in the cross Local Aswad X Zanbaka. Additive genetic variance( Dˆ) was significant for all studied characters, dominance genetic variance(H1,H2) were significant for all characters except H2 for plant height , no. of heads per plant and grain yield which was not significant, these results showed the importance of both additive and dominance genetic components.The average degree of dominance ( a ) value was more than unity indicating the acion of overdominance for all characters.Broad sense(h2 ns) and narrow sense(h2 bs)heritability estimates were high for all characters.